Compartilhar histórias: cadernos de professores em formação - Laura Noemi CHALUH (Universidad de Murcia, 2019)
The purpose of this paper is to examine the practice of writing in the education of teachers in formation, specifically in the full degree of the Pedagogy course of a public university in the State of São Paulo/Brazil, in the context of a discipline that aims the organization of pedagogical work starting from different languages and based on a conception of formation that values the professional and personal dimension. It is a fragment of a larger research that, from a narrative research perspective, considers as object of study my own formative practices in the referred university. In this paper, I focus on the "shared notebook" that is the material produced by a student and it was chosen because it welcome the alternation in the production of the records. Records that bore thoughts and feelings that were aroused in the encounters and that were systematized with words, drawings and other forms of expression. Inspired by the indicative paradigm of Ginzburg (1989), I searched for details in my own memories in the student's shared notebook, reading her records, mine, and those of other colleagues in the group. In this movement of searching for details, I sought a possible configuration of a story that, when unveiled in the deepening of the narrative, explicit some pedagogical knowledge. This work contributes to broaden the understanding the meaning of thinking Education in a narrative way.